Vocal sequential exchanges and intragroup spacing in the Northern Muriqui Brachyteles arachnoides hypoxanthus - Mendes, Francisco Dyonísio Cardoso (2004)
ABSTRACT: Sequential exchanges of vocalizations (staccatos and neighs) emitted by Northern Muriquis Brachyteles arachnoides hypoxanthus were recorded at the Biological Station of Caratinga, Minas Gerais State, Brazil. Staccatos and neighs containing larger proportion of short elements were preferentially produced during short-range exchanges; neighs, produced by a larger number of participants, were typical of long-range exchanges. Staccatos emitted by animals feeding in a dispersed manner contained a larger proportion of tonal elements than those emitted by muriquis feeding in a cohesive manner. Sequential exchanges seem thus to be constituted by two inter-related subsystems of calls that aid muriquis to coordinate intragroup spacing, despite the poor visibility of the habitat.